Banking Union as a Shock Absorber - Ansgar Belke; Daniel Gros (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
This study investigates the shock-absorbing properties of a banking union by providing a detailed comparison between the way regional financial shocks have been absorbed at the federal level in the US, but have led to severe regional (national) financial dislocation and tensions in the euro area. The extent to which the institutions of the banking union, which is now emerging in the euro area, should increase its capacity to deal with future regional boom and bust cycles is also discussed. Cross-border capital flows in the form of equity appear to be much more stable than those taking the form of credit, especially inter-bank credit. Moreover, credit booms and bust leave a debt overhang and losses can materialise only via insolvencies, whereas equity flows absorb automatically losses in case of a bust and provide the cross border owner with incentives to continue to provide financing. It follows that cross-border banks can absorb regional shocks. But large banks pose the 'too big to fail' problem and they would also propagate regional shocks, especially if they originate in large countries, to the entire area.
Keywords: E42; E50; F3; G21; 330; banking union; currency union; default; shock absorber; two-tier reinsurance system